Solve the system of equations.
![Solve the system of equations class=](https://us-static.z-dn.net/files/d7f/a0b7121c042bcf274dfbf6eb86a370e1.jpg)
Answer:
(0, 6 )
Step-by-step explanation:
Given the 2 equations
- 6y + 11x = - 36 → (1)
- 4y + 7x = - 24 → (2)
Multiplying (1) by 4 and (2) by - 6 and adding the result will eliminate y
- 24y + 44x = - 144 → (3)
24y - 42x = 144 → (4)
Add (3) and (4) term by term
2x = 0 ⇒ x = 0
Substitute x = 0 in either of the 2 equations and solve for y
Substituting in (1)
- 6y + 11(0) = - 36, that is
- 6y = - 36 ( divide both sides by - 6 )
y = 6
Solution is (0, 6 )